Characterisation of detachment in the MAST-U Super-X divertor using multi-wavelength imaging of 2D atomic and molecular emission processes. (16th March 2023) - Wijkamp, T.A.; Allcock, J.S.; Feng, X.; Kool, B.; Lipschultz, B.; Verhaegh, K.; Duval, B.P.; Harrison, J.R.; Kogan, L.; Lonigro, N.; Perek, A.; Ryan, P.; et al.
Abstract: In this work, we provide the first 2D spatially resolved description of radiative detachment in MAST-U Super-X L-mode divertor plasmas. The Super-X magnetic configuration was designed to achieve reduced heat- and particle loads at the divertor target compared to conventional exhaust solutions. We use filtered camera imaging to reconstruct 2D emissivity profiles in the poloidal plane for multiple atomic and molecular emission lines and bands. A set of deuterium fuelling scans is discussed that, together, span attached to deeply detached divertor states observed in MAST-U. Emissivity profiles facilitate separate analysis of locked-mode induced split branches of the scrape-off layer. Molecular deuterium Fulcher band emission front tracking reveals that the deuterium electron-impact ionisation front, for which it serves a proxy, detaches at different upstream electron densities in the split branches. Upon detachment of this ionisation front, Balmer emission attributed to molecular activated recombination appears near-target. We report a simultaneous radial broadening of the emission leg, consistent with previous SOLPS-ITER modelling. With increased fuelling this emission region detaches, implying electron temperatures below ∼ 1 eV. In this phase, 2D Balmer line ratio reconstruction indicates an onset of volumetric direct electron-ion recombination near-target. At the highest fuelling rates this emission region moves off-target, suggesting a drop in near-wall electron density accompanying the low temperatures.